Technical Considerations and Fluoroscopy in Percutaneous Fixation of the Pelvis and Acetabulum. Issue 24 (15th December 2019) - Banaszek, Daniel; Starr, Adam J.; Lefaivre, Kelly A.
Abstract : Surgical treatment of the pelvic ring and acetabulum continues to evolve. Improved imaging technology and means for closed reduction have meant that percutaneous techniques have gained popularity in the treatment of the pelvic ring and, more recently, in the acetabulum. Potential benefits include decreased soft-tissue dissection, blood loss, and surgical time. However, these are technically demanding procedures that require substantial expertise from both the surgeon and the radiographer. This article details the necessary fluoroscopic views and general methods used in percutaneous techniques around the pelvis and acetabulum. Despite most studies reporting good-to-excellent clinical and radiographic results, further work is needed to facilitate standardization and optimization of these outcomes.